2019
DOI: 10.5964/jnc.v5i2.164
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in numerical comparison is independent of numerical precision

Abstract: Numeracy, as measured by performance on the non-symbolic numerical comparison task, is a key construct in numerical and mathematical cognition. The current study examines individual variation in performance on the numerical comparison task. We contrast the hypothesis that performance on the numerical comparison task is primarily due to more accurate representations of numbers with the hypothesis that performance dependent on decision-making factors. We present data from two behavioral experiments and a mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
(42 reference statements)
0
7
2
Order By: Relevance
“…The correlations between the performance of numerosity comparison and numerosity estimation reached a significant level ( r = −0.17, p < 0.01), suggesting a relationship between numerosity comparison and estimation. The results were contrary to our prediction, which was based on previous studies ( Guillaume et al, 2016 ; Prather, 2019 ). The correlations between the CR in numerosity comparison, AER in numerosity estimation, and AER in proportion estimation reached the significance level with AER in the numerosity estimation ( r = 0.30, p < 0.001) and proportion estimation ( r = 0.20, p < 0.01) tasks.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The correlations between the performance of numerosity comparison and numerosity estimation reached a significant level ( r = −0.17, p < 0.01), suggesting a relationship between numerosity comparison and estimation. The results were contrary to our prediction, which was based on previous studies ( Guillaume et al, 2016 ; Prather, 2019 ). The correlations between the CR in numerosity comparison, AER in numerosity estimation, and AER in proportion estimation reached the significance level with AER in the numerosity estimation ( r = 0.30, p < 0.001) and proportion estimation ( r = 0.20, p < 0.01) tasks.…”
Section: Resultscontrasting
confidence: 99%
“…However, evidence from adult studies is not as clear cut as that found in developmental studies; many studies have pointed out that the relationship is inconsistently observed in adults (Yeo et al, 2019;Yeo and Price, 2021). For example, there is evidence that ANS acuity indirectly reflects only certain domains of math achievement in adults (Inglis et al, 2011;Patalano et al, 2015;Cho, 2016, 2018).Scholars have pointed out that a possible reason for the mixed results might be that different tasks have been used to measure both ANS ability and mathematics achievement (Lindskog et al, 2013;Prather, 2019). The ANSrelated tasks used in each study for the purpose of assessing ANS ability have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other, there is always a decision process underlying the response of the participants, independent of the actual modality. Recently, it was argued based on two behavioural experiments and a mathematical model that the precision of the numerical representation is not the main driver of the behaviour, instead general decision‐making processes drive the observed performance 54 . Because VGPs showed improved probabilistic inference, 55 the reported differences might solely be due to differences in the decision‐making process.…”
Section: Discussionmentioning
confidence: 99%